Digitalisasi Manajemen Keuangan Melalui Aplikasi Buku Warung Untuk Meningkatkan Kemandirian Ekonomi Pesantren Jabal Rahmah, Kabupaten Solok - Sanda Patrisia Komalasari; Alfairah Azmi; Muhammad Iqbal Abdi Lubis; Rizka Hadelina; Ainul Mardiah; Rizki Dafa Naldi; Rafki Harzikra; Bunga Jacinda; Khalilul Rahman (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
This activity aims to strengthen this independence by integrating digital technology solutions into the school's financial management system. The method used was a participatory qualitative approach with four main stages: preparation, implementation, mentoring, and evaluation. This process involved the active participation of the school's administrators. The implemented solution focused on the use of the digital application